Wayang-Inspired Modern Character Design for Visual Communication - Nugroho, Aris Sarwo; Widiastuti, Santi (International Journal of Graphic Design, 2024)
This research aims to develop a modern character design model based on traditional Javanese puppet figures (wayang), integrating cultural symbolism and contemporary design principles. The study explores how traditional elements, such as color, form, and symbolism in characters like Gatotkaca and Semar, can be adapted into modern, visually appealing designs suitable for today’s media platforms. Using a qualitative-descriptive approach, data were collected through interviews with cultural experts, focus group discussions with graphic designers and young audiences, and surveys to evaluate prototype designs. The findings show that while modern visual elements, such as minimalism and vibrant colors, are highly favored by younger audiences, maintaining the cultural essence of traditional puppetry is crucial. The designs were generally well-received, though some aspects of cultural symbolism required clearer presentation to enhance audience understanding. The research provides practical insights for designers in the creative industry to incorporate traditional cultural elements into digital media, such as animations, video games, and branding campaigns. It also offers theoretical contributions by expanding the understanding of integrating cultural heritage into modern design processes. Future research could explore the application of these characters in interactive platforms such as augmented and virtual reality, as well as investigate more effective ways to present cultural symbolism for global audiences.